DAYA HAMBAT INFUSED WATER JAHE PUTIH (Zingiber officinale var. amarum) TERHADAP PERTUMBUHAN BAKTERI STAPHYLOCOCCUS SP - Ari Khusuma (Jurusan Teknologi Laboratorium Medis, Poltekkes Kemenkes Denpasar, 2022)
The bacteria found in the sputum of patients with cough due to respiratory tract infections are Streptococcus bacteria and Staphylococcus aureus. Symptoms of cough can be treated with herbal remedies, one of which is drinking water from fruit juices, vegetables, herbs, and spices or what is later known as infused water. Plants that are believed to be able to inhibit bacterial growth are white ginger (Zingiber officinale var. amarum) because based on the results of phytochemical identification, ginger contains essential oil compounds and phenolic compounds that are antibacterial. This research aims to determine the inhibition of white ginger infused water on the growth of Staphylococcus sp. This research is a True Experiment with Completely Randomized Design (CRD), with white ginger infused water treatment with various concentrations. The results of the isolation and identification of sputum samples found Staphylococcus sp. The results of the sensitivity test of white ginger infused water as an antibacterial against Staphylococcus sp at all concentrations of 100%, 80%, 60%, and 40% were unable to inhibit the growth of Staphylococcus sp. The results showed that white ginger (Zingiber officinale var. amarum) infused water had no effect on inhibiting the growth of Staphylococcus sp.